2023
DOI: 10.1002/jcsm.13311
|View full text |Cite
|
Sign up to set email alerts
|

One‐year change in sarcopenia was associated with cognitive impairment among haemodialysis patients

Abstract: BackgroundOur study aimed to evaluate change in sarcopenia, its defining components over 1 year follow‐up and investigate associations with subsequent cognitive decline, incident mild cognitive impairment (MCI) and dementia among patients undergoing haemodialysis (HD).MethodsIn the multicentre, longitudinal study, 1117 HD patients aged 56.8 ± 14.3 years (654 men; and 463 women) from 17 dialysis centres in Guizhou Province, China, were recruited in 2019 and followed up for 1 year in 2020. Sarcopenia was diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
(106 reference statements)
2
6
0
Order By: Relevance
“…Age, baseline nutritional status, and physical activity level are key variables that may influence handgrip strength [ 42–44 ]. In addition, previous studies have shown that dialysis treatment leads to muscle atrophy, which reduces handgrip strength [ 45 ], whereas transplantation may have beneficial effects on muscle strength in patients with end-stage renal disease [ 46 ]. These characteristics may have various implications for heterogeneous samples, thus making the external validity of this meta-analysis challenging for generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Age, baseline nutritional status, and physical activity level are key variables that may influence handgrip strength [ 42–44 ]. In addition, previous studies have shown that dialysis treatment leads to muscle atrophy, which reduces handgrip strength [ 45 ], whereas transplantation may have beneficial effects on muscle strength in patients with end-stage renal disease [ 46 ]. These characteristics may have various implications for heterogeneous samples, thus making the external validity of this meta-analysis challenging for generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a syndrome characterized by the progressive loss of skeletal muscle mass, strength, and function ( 29 , 30 ). Sarcopenia status may constantly change; therefore, the longitudinal assessment of sarcopenia is important.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sarcopenia in cirrhotic patients is considerably reported with a wide variety due to the differences in sample size, ethnicity, diagnostic criteria, assessment procedures, and diagnostic thresholds for sarcopenia ( 26 , 30 , 33 , 34 ). A previous meta-analysis found the prevalence in patients with cirrhosis was 37.5% ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations